Characteristic approximation properties of quadratic irrationals - W. B. Jurkat; A. Peyerimhoff (International Journal of Mathematics and Mathematical Sciences)
Some characteristic approximation properties of quadratic irrationals are studied in this paper. It is shown that the limit points of the sequence δn form a subset C(x), and D(x) can be generated from C(x) in a relatively simple way. Another proof of Lekkerkerker's theorem is given using relations between δn−1, δn, δn+1 which are independent of x and n.